Diversity oriented synthesis of tricyclic compounds from glycals using the ferrier and the pauson-khand reactions - Hotha, Srinivas; Tripathi, A. (Journal of Combinatorial Chemistry, 2005)
Diversity oriented synthesis of tricyclic compounds was achieved using a combination of the Ferrier reaction and the Pauson-Khand reaction. Ferrier reaction was effected using NbCl5, and the Pauson-Khand reaction was carried out using CO2(CO)(8), acetonitrile-dimethoxyethane. Michael additions using various alkyl, aryl, and heterocyclic thiols were also performed successfully. The Ferrier, Pauson-Khand, and Michael addition reactions were found to be highly diastereoselective.

Expedient synthesis of 1,2,3-triazole-fused tetracyclic compounds by intramolecular Huisgen ('click') reactions on carbohydrate-derived azido-alkynes - Hotha, Srinivas; Anegundi, Ramakrishna I.; Natu, A. A. (Tetrahedron Letters, 2005)
An efficient, practical and convenient synthesis of 1,2,3-triazole-fused tetracyclic compounds was achieved by intramolecular 1,3-dipolar cycloaddition of carbohydrate-derived azido-alkynes. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: carbohydrates; Click chemistry; Cycloaddition; diversity oriented synthesis; Huisgen reaction

Gold nanoparticle networks with photoresponsive interparticle spacings - Sidhaye, D. S.; Kashyap, Sudhir; Sastry, M.; Hotha, Srinivas; Bhagavatula L. V. Prasad (Langmuir, 2005)
Photoresponsive gold nanoparticle networks were prepared by functionalizing them with azobenzene derivatives. A network can be formed when a linker molecule constituting the azobenzene moiety suitably derivatized on either side with gold surface sensitive groups such as thiols and amines is added to the nanoparticle solution. It is shown that the interparticle spacing in the networks could be controlled by the reversible trans-cis isomerization of the azobenzene moiety induced by UV and visible light, respectively. The photoinduced variation in the interparticle spacings is inferred by the changes in the optical spectra of the gold nanoparticles which display a red or blue shift in the surface plasmon resonance peak depending on a decrease or increase in the interparticle spacing, respectively. Transmission electron microscopy images are in consonance with the evidence from the optical spectra.

Niobium(V) chloride catalyzed microwave assisted synthesis of 2,3-unsaturated O-glycosides by the Ferrier reaction - Hotha, Srinivas; Tripathi, A. (Tetrahedron Letters, 2005)
NbCk catalyzes the Ferrier reaction of per-O-acetylated glycals with primary, secondary, altylic, benzylic and monosaccharide alcohols to give 2,3-unsaturated alpha-glycosides in short reaction times under microwave irradiation conditions. (c) 2005 Elsevier Ltd. All rights reserved.

Stereoselective synthesis of spiroannulated cyclopentenones by the Pauson-Khand reaction on carbohydrate derived enynes - Hotha, Srinivas; Maurya, S. K.; Gurjar, M. K. (Tetrahedron Letters, 2005)
The stereoselective synthesis of spiroannulated cyclopentenones by the Pauson-Khand reactions on hexose and pentose derived enynes was achieved under carbon monoxide free conditions using a stoichiometric quantity of Co-2(CO)(8). The cobalt complex of the alkyne was cleaved using dimethoxyethane-acetonitrile at 85 degrees C to furnish spiroarmulated cyclopentenones in 75-94% yields. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: carbohydrates; cyclopentenone; diversity oriented synthesis; Pauson-Khand reaction

Propargyl glycosides as stable glycosyl donors: anomeric activation and glycoside syntheses - Hotha, Srinivas; Kashyap, Sudhir (Journal of the American Chemical Society, 2006)

Synthesis of spiroannulated dihydroisobenzofuranylated monosaccharides - Maurya, S. K.; Hotha, Srinivas (Tetrahedron Letters, 2006)
An efficient synthesis of spiroannulated dihydroisobenzofurans is achieved using easily accessible carbohydrate-derived furanyl propargyl ethers via an AuCl3 promoted intramolecular Diels-Alder (IMDA) reaction. The scope of the spiroannulation protocol was demonstrated using a diverse range of pentofuranosyl, hexofuransoyl and hexopyranosyl derived substrates in order to synthesize spiroannulated dihydroisobenzofurans. The reaction is high yielding, moisture tolerant, fast and uses only a catalytic amount of AuCl3. (c) 2006 Elsevier Ltd. All rights reserved.

Controlled aggregation of gold nanoparticle networks induced by alkali metal ions - Tamang, Sudarsan; Hotha, Srinivas; Bhagavatula L. V. Prasad (Journal of Nanoscience and Nanotechnology, 2007)
Gold nanoparticle networks were obtained by linking them with cysteine modified triethyleneglycols. The oligo-ether linker molecule initially having a linear structure probably adopts a crown ether type structure upon complexation with alkali metal ions that leads to a controlled aggregation of the network. The extent of aggregation depends on the degree of conformational change in the molecule upon complexation with the metal ion, which in turn is governed by the metal ion radius leading to a dependence of red shift of the surface plasmon resonance on the metal ion radius. Since this network is present in the organic solvent they also act as phase transferring agent for the alkali metal ions from aqueous to organic media.
Keywords: Aggregation; Alkali Metal Ions; Au Nanoparticles; Crown Ether; Surface Plasmon Resonance

Propargyl 1,2-orthoesters as glycosyl donors: stereoselective synthesis of 1,2-trans glycosides and disaccharides - Sureshkumar, Gopalsamy; Hotha, Srinivas (Tetrahedron Letters, 2007)
Propargyl 1,2-orthoesters are identified as glycosyl donors. Various glycosides and disaccharides were synthesized in a stereoselective manner using AuBr3 as the promoter. AuBr3 may activate the alkyne resulting in the formation of a 1,2-dioxolenium ion and also behaves as a Lewis acid to facilitate the attack of the glycosyl acceptor. The versatility of the protocol was demonstrated using a panel of aglycones comprising aliphatic, alicyclic, steroidal and sugar alcohols. (C) 2007 Elsevier Ltd. All rights reserved.

Synthesis of C-2 methylene glycosides from C-2 propargyloxymethyl glycals exploiting the alkynophilicity of AuCl3 - Kashyap, Sudhir; Vidadala, Srinivasa Rao; Hotha, Srinivas (Tetrahedron Letters, 2007)
C-2 Methylene glycosides were synthesized from C-2 propargyloxymethyl glycals in a stereoselective manner using a catalytic quantity of AuCl3. The Au-catalyzed reaction was explored using various aglycones. The current protocol enables the preparation of C-2 methylene glycosides, tolerates diverse functional groups and is fast, catalytic and mild. (c) 2007 Elsevier Ltd. All rights reserved.

Gold mediated glycosylations: selective activation of propargyl 1,2-orthoesters in the presence of aglycones containing a propargyl moiety - Sureshkumar, Gopalsamy; Hotha, Srinivas (Chemical Communications, 2008)
Selective activation of propargyl 1,2-orthoesters in the presence of propargyl glycosides and propargyl ethers was studied; a catalytic amount of AuBr(3) activated the propargyloxy, group of the 1,2-orthoester thereby giving access to disaccharides with the propargyl group at the reducing end; furthermore, propargyl ethers were unaffected under the reaction conditions.

Synthesis of 1,2,3-triazole and 1,2,3,4-tetrazole-fused glycosides and nucleosides by an intramolecular 1,3-dipolar cycloaddition reaction - Anegundi, Ramakrishna I.; Puranik, Vedavati G.; Hotha, Srinivas (Organic & Biomolecular Chemistry, 2008)
Various 1,2,3-triazole and 1,2,3,4-tetrazole fused multi-cyclic compounds were synthesized from carbohydrate derived azido-alkyne and azido-cyanide substrates. The acid sensitive 1,2-O-isopropylidene group of the furanosyl sugar was utilized for diversification to glycosides and nucleosides under Fischer glycosidation and Vorbruggen's conditions, respectively.

Tunable surface modification of silica nanoparticles through `click' chemistry - Chandran, S. Prathap; Hotha, Srinivas; Bhagavatula L. V. Prasad (Current Science, 2008)
Tuning the surface functionality of silica nanoparticles through a `click' chemistry-based protocol is demonstrated. Pyrene, a fluorophore that displays excimer emission specifically at higher density/concentration is chosen for highlighting the fidelity of surface functionalization. The UV-visible absorbance of the pyrene chromophore capping the nanoparticle is used to determine the amount of pyrene units present on the surface of a silica nanoparticle.
Keywords: pyrene; silica nanoparticles; surface functionality; `Click' chemistry

Dendritic effect of ligand-coated nanoparticles: enhanced apoptotic activity of silica-berberine nanoconjugates - Halimani, Mahantappa; Chandran, S. Prathap; Kashyap, Sudhir; Jadhav, V. M.; Bhagavatula L. V. Prasad; Hotha, Srinivas; Maiti, Souvik (Langmuir, 2009)
We describe the synthesis and biological characterization of a novel prototype, namely, silica nanoconjugates bearing a covalently linked berberine, a plant alkaloid known to have antiproliferative activity. The effect of synthesized nanoconjugates on cell proliferation, the cell cycle profile, and apoptosis in the human cervical carcinoma cell line (HeLa), human hepatocellular liver carcinoma cell line (HepG2), and human embryonic kidney (HEK) 293T cell line has been studied and compared with the results obtained for free berberine. Our results show that all the nanoconjugates display higher antiproliferative activity than free berberine. The ability of these nanoconjugates to inhibit cellular proliferation is mediated by the cell cycle arrest at the G1 phase. Moreover, silica nanoconugates caused selective apoptotic arrest with a higher efficiency than free berberine followed by apoptotic cell death as shown by quantitative fluorescence-activated cell sorting analyses. Efficiency of the nanoconjugates increases upon an increase in the linker chain length, demonstrating the distinct role of the spacer chain that conjugates nanoparticles and ligands. The actual reason to show enhanced efficiency by the nanoconjugates has not been elucidated in the present study; however, we hypothesize that an increase in local concentration due to the confinement of a ligand on the nanosurface (''dendritic'' effect) might have led to the observed effect.

Methyl glycosides are identified as glycosyl donors for the synthesis of glycosides, disaccharides and oligosaccharides - Vidadala, Srinivasa Rao; Hotha, Srinivas (Chemical Communications, 2009)
Stable methyl glycosides are identified as glycosyl donors in the presence of AuBr(3) in acetonitrile; a panel of aglycones comprising aliphatic, alicyclic, steroidal and sugar alcohols are examined successfully for the glycosylation reaction and methyl glycosides of di- and tri-saccharides are converted to corresponding tri- and tetra-saccharides exploiting salient features of our novel activation protocol.

Orthogonal activation of propargyl and n-pentenyl glycosides and 1,2-orthoesters - Vidadala, Srinivasa Rao; Thadke, Shivaji A.; Hotha, Srinivas (Journal of Organic Chemistry, 2009)
An orthogonal activation strategy with propargyl and n-pentenyl glycosides has been identified. According to this methodology, n-pentenyl glycosides can be selectively activated with NIS/TMSOTf in the presence of either armed or disarmed propargyl O-glycosides. In addition, we report herein that propargyl 1,2-orthoesters can be selectively activated with AuBr(3) in CH(2)Cl(2) at room temperature in the presence of n-pentenyl glycosides. Similarly, pentenyl 1,2-orthoesters can be selectively activated with NIS/Yb(OTf)(3) in the presence of propargyl glycosides.

Clicking molecular hooks on silica nanoparticles to immobilize catalytically important metal complexes: the case of gold catalyst immobilization - Ganai, Anal Kumar; Bhardwaj, Rima; Hotha, Srinivas; Sen Gupta, Sayam; Bhagavatula L. V. Prasad (New Journal of Chemistry, 2010)
Gold mediated reactions have emerged as one of the best choices for affecting a variety of chemical transformations with a wide range of functional group tolerance. Application of such transformations to industrial processes necessitates immobilization of the Au ions into a matrix for easy separation of the catalyst after reaction. We report the synthesis and characterization of silica nanoparticles in which Au(III) has been immobilized through a 1,2,3-triazole linkage using an alkynalated picolinic acid exploiting ``click chemistry''. The Au( III) immobilized silica nanoparticle has been thoroughly characterized using FT-IR, C-13 CP MAS NMR and XPS. The utility of these particles as an easily separable catalyst for the Hashmi phenol synthesis is also reported.

Gold-catalyzed glycosidations: synthesis of 1,6-anhydro saccharides - Thadke, Shivaji A.; Hotha, Srinivas (Tetrahedron Letters, 2010)
Various 1,6-anhydro sugars are synthesized utilizing salient features of gold-catalyzed glycosidations. All the reactions occurred under mild conditions in the presence of 7 mol % of AuBr(3) enabling easy synthesis of 1,6-anhydro sugars from corresponding 6-hydroxy propargyl/methyl monosaccharides, disaccharides, and trisaccharides in good yields. (C) 2010 Elsevier Ltd. All rights reserved.

Gold-catalyzed glycosidations: unusual cleavage of the interglycosidic bond while studying the armed/disarmed effect of propargyl glycosides - Kayastha, Abhijeet K.; Hotha, Srinivas (Tetrahedron Letters, 2010)
Armed/disarmed effect of propargyl glycosides in the presence of AuBr(3) is studied. Observed that oxophilic AuBr(3) cleaves interglycosidic bond of an armed disaccharide resulting in the formation of a disaccharide and a 1,6-anhydro sugar. Trisaccharides were obtained after fine tuning the reactivity of the glycosyl donor with different protecting groups. (C) 2010 Elsevier Ltd. All rights reserved.

Enhanced DNA binding of 9-omega-amino alkyl ether analogs from the plant alkaloid berberine - Islam, Md Maidul; Basu, Anirban; Hossain, Maidul; Sureshkumar, Gopalsamy; Hotha, Srinivas; Kumar, Gopinatha Suresh (DNA and Cell Biology, 2011)
To understand the structure-activity relationship of isoquinoline alkaloids, absorption, fluorescence, circular dichroism, and thermodynamics were employed to study the interaction of five C-9-omega-amino alkyl ether analogs from the plant alkaloid berberine with double-stranded calf thymus DNA. The C-9 derivatization resulted in dramatic enhancements in the fluorescence emission of these compounds. The most remarkable changes in the spectral and binding properties were in the BC4 and BC5 derivatives. Interactions of these analogs, which have an additional recognition motif with DNA, were evaluated through different spectroscopic and calorimetric titration experiments. The analogs remarkably enhanced the DNA binding affinity and the same was directly dependent on the alkyl chain length. The analog with six alkyl chains enhanced the DNA binding affinity by about 33 times compared with berberine. The binding became more entropically driven with increasing chain length. These results may be of potential use in the design of berberine derivatives and understanding of the structure-activity relationship for improved therapeutic applications.

Facile synthesis of unusual glycosyl carbamates and amino acid glycosides from propargyl 1,2-orthoesters as glycosyl donors - Shaikh, Ashif Y.; Sureshkumar, Gopalsamy; Pati, Debasish; Sen Gupta, Sayam; Hotha, Srinivas (Organic & Biomolecular Chemistry, 2011)
Propargyl 1,2-O-orthoesters are exploited for the synthesis of 1,2-trans O-glycosides of protected amino acids. N-Fmoc- and N-Cbz protected serine/threonine - benzyl/methyl esters reacted well with glucosyl-, galactosyl-, mannosyl- and lactosyl- derived propargyl 1,2-orthoesters affording respective 1,2-trans glycosides in good yields under AuBr(3)/4 angstrom MS Powder/CH(2)Cl(2)/rt. t-Boc serine derivative gave serine 1,2-orthoester and glycosyl carbamate. Optimized conditions enabled preparation of new glycosyl carbamates from N-Boc protected amines in a single step using gold catalysts and propargyl 1,2-orthoesters in excellent yields.

Gold catalyzed glycosidations for the synthesis of sugar acrylate/acrylamide hybrids and their utility - Thadke, Shivaji A.; Kar, Mritunjoy; Sen Gupta, Sayam; Hotha, Srinivas (Carbohydrate Research, 2011)
Propargyl glyco 1,2-orthoesters were exploited for the efficient synthesis of interesting glycomonomers such as glyco-acrylates and acrylamides using gold catalysts. It was observed that propargyl glyco 1,2-orthoesters with hydroxyethyl acrylates gives very good yield of the corresponding glyco-acrylates in a single step in the presence of catalytic amount of gold(III) catalyst; whereas, gold catalyzed glycosidation reaction on hydroxyethyl acrylamides was found to yield the corresponding acrylamidoyl 1,2-orthoester which was then converted to the corresponding glycol-acrylamide in the presence of catalytic amount of TMSOTf. Synthesized glyco-acrylate/acrylamide monomers are shown to undergo thiolate addition as well as free radical polymerization (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: carbohydrates; Glycoacrylamides; Glycoacrylates; Glycopolymers; glycosylation; Gold

Propargyl/methyl furanosides as potential glycosyl donors - Vidadala, Srinivasa Rao; Gayatri, Gaddamannugu; Sastry, G. Narahari; Hotha, Srinivas (Chemical Communications, 2011)
Transfuranosylations are not well studied though many similar studies exist for transpyranosylation; herein, we report that propargyl/methyl D-ribf- and D-lyxf- give only 1,2-trans glycosides whereas D-araf- and D-xylf- result in a mixture of 1,2-trans and 1,2-cis glycosides; observed facts are rationalised by computational studies.

Synthesis of glycopolypeptides by the ring opening polymerization of O-glycosylated-alpha-amino acid N-carboxyanhydride (NCA) - Pati, Debasis; Shaikh, Ashif Y.; Hotha, Srinivas; Sen Gupta, Sayam (Polymer Chemistry, 2011)
The novel synthesis of O-glycosylated lysine-NCA from a stable glycosyl donor and a commercially available protected amino acid in very high yield is reported. These O-glycosylated lysine-NCA monomers underwent ring opening polymerization using simple primary amine initiators to form well defined, high molecular weight homoglycopolypeptides and diblock co-glycopolypeptides. The synthesis of azide labelled end functionalized glycopolypeptides and amphiphilic diblock copolypeptides is also reported. This methodology represents an easy and practical route to the synthesis of O-glycosylated polypeptides with 100% glycosylation.

Controlled synthesis of O-glycopolypeptide polymers and their molecular recognition by lectins - Pati, Debasis; Shaikh, Ashif Y.; Das, Soumen; Nareddy, Pavan Kumar; Swamy, Musti J.; Hotha, Srinivas; Sen Gupta, Sayam (Biomacromolecules, 2012)
The facile synthesis of high molecular weight water-soluble O-glycopolypeptide polymers by the ring-opening polymerization of their corresponding N-carboxyanhydride (NCA) in very high yield (overall yield > 70%) is reported. The per-acetylated-O-glycosylated lysine-NCA monomers, synthesized using stable glycosyl donors and a commercially available protected amino acid in very high yield, was polymerized using commercially available amine initiators. The synthesized water-soluble glycopolypeptides were found to be alpha-helical in aqueous solution. However, we were able to control the secondary conformation of the glycopolypeptides (alpha-helix vs nonhelical structures) by polymerizing raceznic amino acid glyco NCAs. We have also investigated the binding of the glycopolypeptide poly(alpha-manno-O-lys) with the lectin Con-A using precipitation and hemagglutination assays as well as by isothermal titration calorimetry (ITC). The ITC results clearly show that the binding process is enthalpy driven for both alpha-helical and nonhelical structures, with negative entropic contribution. Binding stoichiometry for the glycopolypeptide poly(alpha-manno-O-lys) having a nonhelical structure was slightly higher as compared to the corresponding polypeptide which adopted an alpha-helical structure.

Engineered glucose to generate a spectroscopic probe for studying carbohydrate biology - Tripathi, Ashish; Singh, Vibha; Aishwarya, K. G.; Aradhyam, Gopala Krishna; Hotha, Srinivas (Advances in Experimental Medicine and Biology, 2012)

Synthesis and self-assembly of amphiphilic homoglycopolypeptide - Dhaware, Vinita; Shaikh, Ashif Y.; Kar, Mrityunjoy; Hotha, Srinivas; Sen Gupta, Sayam (Langmuir, 2013)
The synthesis of the amphiphilic homoglycopolypeptide was carried out by a combination of NCA polymerization and click chemistry to yield a well-defined Polypeptide having an amphiphilic carbohydrate on its side chain. The amphiphilicity of the carbohydrate was achieved by incorporation of an alkyl chain, at the C-6 position of the carbohydrate thus also rendering the homoglycopolypeptide amphiphilic. The homoglycopolypeptide formed multimicellar aggregates in water above a critical concentration of 0.9 mu M due to phase separation. The multimicellar aggregates were characterized by DLS, TEM, and AFM. It is proposed that hydrophobic interactions of the aliphatic chains at the 6-position of the sugar moieties drives the assembly of these rod-like homoglycopolypeptide into large;spherical aggregates. These multimicellar aggregates encapsulate both hydrophilic as well as hydrophobic dye as was confirmed by confocal microscopy. finally, amphiphilic random polypeptides containing 10% and 20% alpha-D-mannose in addition to glucose containing a, hydrophobic alkyl chain at its 6 position were synthesized by our methodology, and these polymers Were also found to assemble into spherical nanostructures. The spherical assemblies Of amphiphilic random glycopolypeptides containing 10% and 20% mannose were found to be surface bioactive and were found, to interact with the lectin Con-A.

Tetrazine templated method for the synthesis of ternary conjugates - Rao, Boddu Venkateswara; Dhokale, Snehal A.; Rajamohanan, Pattuparambil R.; Hotha, Srinivas (Chemical Communications, 2013)
Conjugation is an important reaction that enables coupling of molecules. Many protocols exist for the synthesis of binary conjugates from two different molecules or for the polyvalent display of a singlemolecule. There aren'tmanymethods for the synthesis of ternary conjugates. However, methods for ternary conjugation are important for understanding the interplay of interactions between three biomolecules (or any three molecules per se). A strategy for ternary bioconjugation using inverse electron demand Diels-Alder reaction with tetrazine is studied. Ternary conjugation was demonstrated by the reaction of a model glyco-peptide binary conjugate with a fluorescent tagged olefin.

Cationic charged helical glycopolypeptide using ring opening polymerization of 6-deoxy-6-azido-glyco-N-carboxyanhydride - Shaikh, Ashif Y.; Das, Soumen; Pati, Debasis; Dhaware, Vinita; Sen Gupta, Sayam; Hotha, Srinivas (Biomacromolecules, 2014)
Glycopolypeptides with a defined secondary structure are of significance in understanding biological phenomena. Synthetic glycopolypeptides, or polypeptides featuring pendant carbohydrate moieties, have been of particular interest in the field of tissue engineering and drug delivery. In this work, we have synthesized charged water-soluble glycopolypeptides that adopt a helical conformation in water. This was carried out by the synthesis of a glyco-N-carboxyanhydride (glyco-NCA) containing an azide group at the sixth position of the carbohydrate ring. Subsequently, the NCA was polymerized to obtain azide-containing glycopolypeptides having good control over molecular weight and polydispersity index (PDI) in high yields. We were also able to control the incorporation of the azide group by synthesizing random co-glycopolypeptide containing 6-deoxy-6-azido and regular 6-OAc functionalized glucose. This azide functionality allows for the easy attachment of a bioactive group, which could potentially enhance the biological activity of the glycopolypeptide. We were able to obtain water-soluble charged glycopolypeptides by both reducing the azide groups into amines and using CuAAC with propargylamine. These charged glycopolypeptides were shown to have a helical conformation in water. Preliminary studies showed that these charged glycopolypeptides showed good biocompatibility and were efficiently taken up by HepG2 cells.

Unravelling the prebiotic origins of the simplest α-ketoacids in cometary ices: a computational investigation - Dash, Soumya Ranjan; Pandya, Rinu; Singh, Geetika; Sharma, Himanshu; Das, Tamal; Haldar, Hritwik; Hotha, Srinivas; Vanka, Kumar (CHEMICAL COMMUNICATIONS, 2024)
Keywords: GLYOXYLATE; Hydrocarbons; Metabolism; Precursors